Psikologi Individu Alfred Adler: Konseling Islam Berbasis Pancasila Pada Mahasiswa BPI Universitas Muhammadiyah Parepare: Islamic Counseilng, Alfred Adler’s Counseling Techniques, Pancasila Pillars - Susanto, Junaedi Dwi (Jurusan Bimbingan dan Penyuluhan Islam, 2025)
The development of the world of education today faces many sociocultural phenomena that affect the quality of students' self, so that positive adaptation is needed to face various negative stimuli that occur in the environment. Pancasila-Based Islamic Counseling using Alfred Adler's individual psychology perspective is expected to form the best construct in the therapeutic world. In this study, a literature study method is used to find basic concepts so that it can provide a good construct for future research. With the results of this research, concepts and ideas are an integration of Alfred Adler's individual psychology theory and therapy that focuses on solutions using Pancasila-based Islamic counseling. This Islamic counseling provides assistance to students to form, develop their potential in a healthy and productive way when forged by unexpected circumstances to become what they want, ultimately forming a resilient personality. This Islamic counseling helps clients to reach a better stage of self-development by understanding and strengthening self-confidence (in this case the formation of the quality of faith) to be ready to face challenges in life's journey. Keywords: Islamic Counseilng, Alfred Adler’s Counseling Techniques, Pancasila Pillars